Enhancing Firm Efficiency Measurement Using DEA and Fuzzy Approaches with Integrated Corporate Social Responsibility - Gaillard, Gallego; Behrouznia, Keskin (Journal Economic Business Innovation, 2025)
Purpose: We propose a new scientific approach by integrating Corporate Social Responsibility (CSR) into the measurement of firm efficiency through a dynamic fuzzy Data Envelopment Analysis (DEA) model. It aims to investigate the relationship between CSR practices and firm performance over time across industries.Findings: Higher CSR engagement companies appear to obtain better efficiency scores and show resilience when adapting to external challenges. Especially, capital-intensive industries where environmental risk is high benefit most from integrating CSR into their operational structures. The corresponding dynamic fuzzy DEA model introduced by Yang, et al. (2023) successfully analyses the non-neutrality of input metrics on CSR resilience, along with uncertainties inherent in CSR metrics, hence offering valuable insights into their industry-specific and temporal variability.Novelty: This research is the first to apply a dynamic fuzzy DEA approach to integrating CSR in terms of a key measure of firm efficiency. This study fills the gap between sustainability practices and operational performance by addressing the complexity of multifaceted impacts of CSR.Implications: These results provide practical recommendations for policy makers and managers to reflect the reconciliation of environmental or social objectives with financial performance in CSR strategies. Moreover, the methodological framework paves the way for other studies to consider dynamic and uncertain variables into efficiency measurement.